Transforming the rural Asian economy: the unfinished revolution - Rosegrant, Mark W.; Hazell, Peter B. R. (International Food Policy Research Institute, 2001)
Developing Asia as a whole has taken remarkable strides since the food crises of the 1960s. Improvements in food security, poverty reduction, and per capita income initiated by the Green Revolution have been substantial and lasting. Although life has improved for most rural Asians, about 670 million still live in poverty, and they must tolerate lower levels of health, education, and general well-being than their urban counterparts. To complete the economic transformation in rural Asia requires further growth, but growth that is more equitable and environmentally sustainable than it has been in the past. Meeting this challenge will warrant more efficient application of the lessons already learned about agricultural growth, public-sector investment, rural poverty reduction, and natural resource protection. The authors argue that six emerging challenges will also need special attention: (1) Making growth pro-poor; (2) Managing the legacy of the economic crisis; (3) Managing globalization; (4) Revitalizing agricultural research and technology dissemination; (5) Managing land and water scarcity and degradation; and (6) Building good governance and social capital.